Practical Approaches to Build and Sustain a Cardio-Oncology Clinic - Angeliki Chasouraki; Christos Kourek; Alexandros Sianis; Konstantinos Loritis; Peggy Kostakou; Elias Tsougos; Ioannis Paraskevaidis; Argyrios Ntalianis; Alexandros Briasoulis (Journal of Cardiovascular Development and Disease, 2022)
The therapeutical advances in recent years in the field of oncology treatment have increased survival rates and improved the quality of life of oncology patients, thus turning cancer into a chronic disease. However, most of the new cancer treatments come at the expense of serious cardiovascular adverse events threatening the success story of these patients. The establishment of multidisciplinary medical teams to prevent, monitor, and treat cardiovascular diseases in cancer-treated patients is needed now more than ever. The aim of this narrative review is to demonstrate the existing knowledge and practical approaches on how to establish and maintain a cardio-oncology program for the rising number of patients who need it.